(untitled) (Eurasian Research Bulletin, 2022)
In recent years, there has been an increase in the incidence of respiratory pathology, including recurrent and chronic respiratory diseases [2,5,11,14]. Thus, according to the scientists of Uzbekistan and world statistics, acute bronchopulmonary diseases account for 36% in the structure of general morbidity in children and 51% in the cause of infant mortality [11,17].